The expanded inframammary fold triangle: Improved results in large volume breast reductions - Karan Chopra; Kashyap Komarraju Tadisina; Alexandra Conde-Green; Devinder P Singh (Indian Journal of Plastic Surgery)
Context: The inferior pedicle, Wise-pattern reduction mammaplasty is the most popular technique for breast reduction because of its reproducible results and reliability. However, complication rates in super obese patients or patients receiving large volume reductions are high, ranging from 35 to 78%. These complications include delayed healing, infection, seroma, nipple-areolar complex necrosis, fat necrosis and development of hypertrophic scars. Aims: This study aimed to determine whether a modification to the standard Wise-pattern reduction technique, an expanded inframammary fold skin triangle, produces improved outcomes in high-risk large volume breast reduction patients. We report that this modification leads to improved outcomes by decreasing wound complications and improving aesthetic appearance. Settings and Design: Twenty-two patients received the inferior pedicle Wise-pattern reduction mammaplasty, which was modified to include an 8 cm wide inferior pedicle. This pedicle was de-epithelialized and an 8 Χ 3 cm 2 triangle of skin was preserved at the inferior base to reduce tension at the triple point, inverted T-closure. Materials and Methods: A retrospective review was performed on all patients who underwent reduction mammaplasty with the expanded inframammary fold (eIMF) technique as well as all patients who received the standard wise pattern technique. Statistical Analysis Used: A student t-test was performed for both reduction populations using SPSS software package. Statistical significance was defined as P < 0.05. Results: The average patient age was 32.25 years old (range 18-59), average BMI was 35.0, and average tissue mass removed per breast was 1378.39 g. The modified technique was found to produce a statistically significant (P < 0.05) increase in the amount of breast tissue removed (693.96 g increase in the left and 571.21 g in the right) as well as a statistically significant (P < 0.05) reduction in dehiscence (75% reduction) and post-operative infection (44.10%). Conclusions: This method is an easily reproducible and reliable technique that produces a favourable cosmetic outcome with acceptable, sustainable results in high-risk reductions in obese patients.